Basic technical physics - Tippens, Paul E. (New York : McGraw Hill Education, 1983)
The primary objective of this book was to produce an applied physics textbooks that presented the difficult concepts needed for today's job market in such a way that could be easily understood.
Chapter 1. Technical mathematics -- Chapter 2. Technical measurement -- Chapter 3. Force and vectors -- Chapter 4. Equilibrium and friction -- Chapter 5. Torque and rotational equilibrium -- Chapter 6. Uniformly accelerated motion -- Chapter 7. Force and acceleration.
Includes index.
Keywords: PHYSICS -- TECHNICAL